Perioperative rosuvastatin therapy increases creatine kinase and the risk of acute kidney injury in patients undergoing cardiac surgery. (3rd October 2022) - Wijesurendra, R; Sardell, R; Hill, M; Jayaram, R; Samuel, N; Staplin, N; Emberson, J; Collins, R; Zheng, Z; Haynes, R; Casadei, B
Abstract: Introduction: In patients undergoing cardiac surgery, perioperative statin therapy does not prevent atrial fibrillation or myocardial injury, but results in increased creatinine levels after surgery. Here we investigated the incidence of acute kidney injury (AKI) in 1922 patients scheduled for elective cardiac surgery who were randomized to perioperative rosuvastatin (20 mg once daily) or placebo in the Statin Therapy In Cardiac Surgery (STICS) trial. Methods: AKI post-surgery was defined according to international guidelines using plasma creatinine. Biomarkers related to kidney function, muscle injury and inflammation were investigated, including cystatin C, total creatine kinase (CK), troponin I, growth differentiation factor 15 (GDF-15), interleukin-6 (IL-6), procalcitonin, and placental growth factor (PGF). Results: At 48 hours post-surgery, AKI was significantly more common in patients allocated to rosuvastatin compared to placebo when defined by creatinine (24.7% vs 19.3%; OR 1.37 [95% CI 1.10–1.70]; p=0.005; Figure 1A) or by cystatin C (9.2% vs 5.1%; OR 1.86 [95% CI 1.29–2.67]; p<0.001; Figure 1B). Elevations in CK to >10x and >40x baseline level were also more frequent in rosuvastatin-allocated patients compared to placebo (30.9% vs 26.5%, p=0.02, and 2.1% vs 0.7%, p=0.02, respectively; Figure 1C). Post-operative concentrations of troponin I, GDF-15, IL-6, procalcitonin, and PGF were similar between the groups (Table 1). Conclusions: Perioperative rosuvastatin initiation increased the absolute risk of AKI after cardiac surgery by 4–5%. Rosuvastatin also led to greater elevations in post-operative creatine kinase, but did not affect other biomarkers of tissue injury, inflammation, and myocardial injury. Further research is needed to delineate the underlying mechanism of AKI with perioperative rosuvastatin. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation